Loyal Soldier, Fearsome Terrorists: The Hmong as a Martial Race in Southeast Asia and the United States - Alex Hopp (Hmong Studies Journal, 2020)
Martial race theory, an ideological construction used to organize colonial hegemony, acted as a lens through which the French and the United States understood the Hmong in Southeast Asia. In the early 20th century, Laotian Hmong resistance to French colonialism was interpreted as evidence of the martial qualities of the Hmong. Subsequently, a combined French-Hmong resistance against the Japanese occupation of Indochina cemented their “martial” status and both informed and retroactively “justified” the U.S. decision to recruit the Hmong during the Secret War. In the aftermath of the Secret War, the flight of Hmong refugees to the United States brought martial race theory to American soil, evidenced by legislation designed to honor Hmong veterans and by the designation of certain Hmong as terrorists following 9/11. Overall, this classification of the Hmong as a martial race illustrates the ways that colonial legacies remain impactful even today, both for the colonial subject and for the imperial power.